Biographical sketch of Philippe Vandermaelen - Vandermaelen, Philippe, 1795-1869.
Biographical sketch of Vandermaelen by an unknown author together with eulogies.
Facsimile.
French geographer. Full name: Philippe Marie Guillaume Vandermaelen.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Geographers